2019
DOI: 10.21608/adjg.2019.7177.1070
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism by Analysis of Maxillary Sinus Dimensions in a Sample of Egyptian Population Using Cone Beam Computed Tomography

Abstract: Purpose: To assess maxillary sinuses dimensions and the volume using Cone Beam Computed Tomography .Explore whether these parameters can be used to gender determination. Material and methods: Left and Right maxillary sinus images were obtained for one hundred Egyptian patients divided into three age groups and different parameters (length, width, height, perimeter, Area, and volume) were measured and calculated. Mean value and standard deviation of left and right sides of maxillary sinuses measurements were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This study shows that there is sexual dimorphism with most of the FS, MS, IMD and BZD dimensions higher in males with MS and BZD significant. This is similar to other reports [5,10,[23][24][25][26][27][28] but contrary to study by Ariji et al which reported no significant difference between the genders [21]. Our study shows that generally, the left FS has higher dimensions than the right which is similar to other reports [29][30][31][32], but in contrast to another study done in India in which the right FS has higher values [27].…”
Section: Discussionsupporting
confidence: 93%
“…This study shows that there is sexual dimorphism with most of the FS, MS, IMD and BZD dimensions higher in males with MS and BZD significant. This is similar to other reports [5,10,[23][24][25][26][27][28] but contrary to study by Ariji et al which reported no significant difference between the genders [21]. Our study shows that generally, the left FS has higher dimensions than the right which is similar to other reports [29][30][31][32], but in contrast to another study done in India in which the right FS has higher values [27].…”
Section: Discussionsupporting
confidence: 93%
“…In the cancellous bone the trabeculae were thin, allowing ample medullary space, frequently engaged by adipocytes and fat cells leading to bone resorption. (16) In a study about age-related morphological changes of the maxillary sinus which performed on 70 cases (36 males and 34 females, mean: 45.4 years) include each ten cases from the second to seventh decade, six cases in the eighth decades and four cases in the ninth decades. They showed that; the poster-anterior, medial-lateral diameters and the area had their peaks in approximately the third to fifth decades.…”
Section: Discussionmentioning
confidence: 99%
“…The volumetric and surface data of the paranasal sinuses were sorted according to age since the factor of ontogeny considerably affects the shape of these structures (e.g., see Ferreira et al, 2021). The linear distances were sorted according to sex for their value in detecting sexual dimorphism in the sinus anatomy (Bangi et al, 2017; ELbaz et al, 2019; Umeres‐Alvis, 2019). All quantitative data were ordered using spreadsheet software and expressed as averages and standard deviation.…”
Section: Methodsmentioning
confidence: 99%